Escherichia coli Urinary Infection as a Cause of Acute Hemorrhagic Edema in Infancy. Issue 6 (8th October 2015) - Breda, Luciana; Franchini, Simone; Marzetti, Valentina; Chiarelli, Francesco
Abstract: Acute hemorrhagic edema of infancy (AHEI) is a benign leukocytoclastic small‐vessel vasculitis that affects infants, presenting with a classic clinical triad. Because of the self‐limited progression, conservative management is the most common approach. We describe a case of AHEI apparently triggered by an Escherichia coli urinary tract infection.